Efficient ternary catalyst system for the copolymerization of lactide, epoxides and CO2: new insights into the cooperative mechanism. Issue 21 (10th May 2021) - Li, Xiang; Hu, Chen-yang; Duan, Ran-long; Liang, Zhuang-zhuang; Pang, Xuan; Deng, Ming-xiao
Abstract : Ternary catalyst systems (TCSs) are an emerging type of catalyst for the synthesis of multiblock copolymers of lactide (LA), epoxides and CO2 . Abstract : Ternary catalyst systems (TCSs) are an emerging type of catalyst for the synthesis of multiblock copolymers of lactide (LA), epoxides and CO2 . For our previous TCS (SalenCo III -dinitrophenol (DNP), SalenCo II and PPNCl; TCS I), although multiblock copolymers could be successfully prepared from mixed monomers, the low activity from SalenCo II prevents TCS I from being further applied. In this work, a new homogeneous TCS (TCS III) is presented with two substitution strategies of SalenCo II . TCS IIIa consists of SalenCo III -DNP, SalenCo III -difluorothiophenol (DFTP) and PPNCl, while TCS IIIb contains SalenCo III -DNP, oxygen and PPNCl. Compared to TCS I, TCS III showed higher activity (for TCS IIIa, TOFPO increased from 27 h −1 to 231 h −1 ), and remained active even under diluted conditions ([Cat] : [PO] = 1 : 5000), while TCS I lost activity when the ratio was over 1 : 2500. The microstructure of the resultant copolymer was analyzed in detail, the low average chain length being consistent with its thermal property. SalenCo III -DFTP is different from SalenCo III -DNP in the X-axial ligands: the thiophenol endows SalenCo III with special catalytic property, contributing to the higher activity of TCS IIIa . In TCS IIIb, SalenCo II is replaced by the cocatalyst of oxygen, which is beneficial for reduction of SalenCo loading. The results of the TCSs provide key insights into the copolymerization mechanism of LA, epoxide and CO2, and show promising implications for the design of future catalytic systems.